Mapping the Digital Business Landscape: A Systematic Literature Review of Transformation, Governance, and Ecosystem Dynamics (2020–2025) - Umi Suryani; Jovannia Grisella Eka Putri; Irsyad Parama Dwiputra (Digismantech (Jurnal Program Studi Bisnis Digital), 2025)
The digital transformation of global business ecosystems has rapidly reshaped how organizations create value, manage data, and compete in an interconnected economy. The convergence of platformization, artificial intelligence (AI), fintech innovation, and sustainability imperatives has generated complex cross-industry interactions, necessitating a comprehensive synthesis of recent research. Despite the proliferation of studies, existing literature remains fragmented across technological, managerial, and regulatory dimensions. Therefore, this study systematically reviews and integrates current knowledge on digital business between 2020 and 2025, identifying dominant themes, methodological trends, and research gaps shaping the future of digital transformation and governance. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines to ensure methodological transparency and replicability. Searches were performed across Scopus,Web of Science, ScienceDirect, and Google Scholar using Boolean combinations of keywords such as “digital business,” “digital transformation,” “AI,” “platform,” and “data governance.” From 1,132 initial records, 874 unique studies were screened, 148 were fully reviewed, and 18 met all inclusion criteria. Each study was assessed using CASP/JBI quality appraisal tools and analyzed via thematic synthesis through open, axial, and selective coding. Eight core clusters emerged: platformization & ecosystems, digital transformation of SMEs, omnichannel experience, data governance & privacy, AI & automation, fintech & payments, sustainability & social impact, and cross-border global value chains. The synthesis revealed that digital business research has evolved toward ecosystem-based models emphasizing data-driven collaboration, API interoperability, and AI-enabled decision-making. Future success in digital business depends on strategically integrating technology, governance, and sustainability. Further research should focus on quantifying data’s economic value, developing standardized ecosystem governance, and fostering inclusive digital transformation in developing economies.Keywords:  digital business, platform ecosystem, data governance, artificial intelligence, fintech, sustainability